Announcement of Retraction (Islamic Dental Association of Iran, 2015)
The editorial office of the Journal of Islamic Dental Association of Iran has recently determined that an original article entitled "Stress Distribution in Three-Implant- Retained Mandibular Overdentures Using Finite Element Analysis" authored by Ahmadzadeh A, Golmohammadi F, Mousavi N, Epakchi S. published in thewinter 2015 issue of the Journal of Islamic Dental Association of Iran [Journal of Islamic Dental Association of IRAN (JIDAI). 2015;27(1):1.] was subsequently found to have publishing misconduct as well as duplication. Therefore, we hereby notify our readers that this paper was officially retracted.